2019
DOI: 10.1002/cbin.11106
|View full text |Cite
|
Sign up to set email alerts
|

Functional prediction and characterization of Dip2 gene in mice

Abstract: Disconnected interacting protein 2 (DIP2) is a highly conserved protein family among invertebrates and vertebrates, but its function remains unclear. In this paper, we summarized the conservation of gene sequences and protein domains of DIP2 family members and predicted that they may have a similar functional role in acetyl-coenzyme A (acetyl-CoA) synthesis. We then used the most characterized member, disconnected interacting protein 2 homolog A (DIP2A), for further study. DIP2A is a cytoplasmic protein that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…We found the levels of Ac-CoA were down-regulated in Dip2a KO mice, confirming that DIP2A is involved in Ac-CoA synthesis [21]. Optimal protein acetylation requires sufficient levels of Ac-CoA as the sole acetyl group donor [38].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We found the levels of Ac-CoA were down-regulated in Dip2a KO mice, confirming that DIP2A is involved in Ac-CoA synthesis [21]. Optimal protein acetylation requires sufficient levels of Ac-CoA as the sole acetyl group donor [38].…”
Section: Discussionmentioning
confidence: 73%
“…Ac-CoA is an exclusive acetyl donor for lysine residues, and nonenzymatic acetylation has been observed in eukaryotic cells [38]. Our previous study indicates DIP2A is involved in Ac-CoA synthesis [21]. We thus measured Ac-CoA concentration in Dip2a KO brain lysate and found a significantly decreased Ac-CoA concentration in comparison with WT littermates (6.92 ± 0.60 pmol/mg and 5.06 ± 0.55 pmol/mg for WT and KO, respectively; Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the DIP2 family protein consists of three members, namely, DIP2A, DIP2B, and DIP2C located on chromosomes 12q13.12, 21q22.3, and 10p15.3, respectively. Bioinformatic analysis has suggested that mammalian DIP2s (i.e., DIP2A, DIP2B, and DIP2C) contain three putative and conserved functional domains, namely one DNA methyltransferase 1-associated protein 1 (DMAP1)-binding domain (14-131 aa) and two adenosine monophosphate (AMP)-binding domains (370-822 and 1025-1495 aa) with similar roles in acetyl co-enzyme synthesis [2]. The presence of these domains also suggests that the encoded protein may participate in DNA methylation [3].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these domains also suggests that the encoded protein may participate in DNA methylation [3]. The mouse Dip2 gene has three homologs, Dip2A, Dip2B, and Dip2C, distributed on chromosomes 10, 15, and 13, respectively [2]. The mouse Dip2b gene was first isolated from the mouse embryonic E12.5 cDNA library [1].…”
Section: Introductionmentioning
confidence: 99%